Developing a highly pH-sensitive ĸ-carrageenan-based intelligent film incorporating grape skin powder via a cleaner process. (20th January 2020) - Chi, Wenrui; Cao, Lele; Sun, Guohou; Meng, Fansong; Zhang, Cijian; Li, Jian; Wang, Lijuan
Abstract: An intelligent film was prepared from ĸ-carrageenan blended with hydroxypropyl methylcellulose and directly adding anthocyanins-rich grape skin powder (GSP) as the indicator with an extraction-free process. The films were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, and observed by stereo microscope and Scanning electron microscope. The light transmittance, water-adsorption and mechanical properties were determined and tests monitoring pork freshness were conducted to evaluate its potential applications. The results show that the GSP distribution uniformity in the films decreased with GSP content increased; GSP formed new hydrogen bonds with matrix molecules and the cross-sections of the films were smooth and continuous. The appropriate addition of GSP can enhance the compatibility of the matrix, but decrease the film hydrophilicity. With GSP content increasing from 0% to 8%, the light transmittance decreased from 83.10% to 42.89% at 600 nm, and EB% and TS of the films decreased from 19.65% to 11.30% and from 20.96 MPa to 14.25 MPa, respectively. The film became blue-green when the pH reached 7, indicating that it is highly pH-sensitive and the film changed from purple to green when TVB-N was 14.63 mg/100 g, suggesting that it is intelligent for monitoring the freshness of the pork. This study offers a clean path to prepare a highly pH-sensitive film for indicating food freshness. Graphical abstract: Image 1017053 Highlights: ĸ-carrageenan/HPMC films containing grape skin powder (GSP) were prepared. The composite films were highly sensitive to pH changes. The pH-sensing films were potential in indicating the quality of the protein-rich foods.